Black–White Differences in the Link Between Offspring College Attainment and Parents' Depressive Symptom Trajectories. (February 2022) - Yahirun, Jenjira; Sheehan, Connor; Mossakowski, Krysia
This study examines whether the relationship between children's college attainment and their parents' mental health differs for Black and White parents as they age. Data come from the U.S. Health and Retirement Study (HRS) and multilevel growth curve models are used to assess parents' depressive symptom trajectories. Results indicated that parents over age 50 whose children all completed college had significantly lower initial levels of depressive symptoms than those with no college-educated children. The initial benefit was stronger for Blacks than Whites. Results stratified further by parents' education show that Black parents at nearly all levels of schooling experienced stronger returns to their mental health from children's college completion compared to White parents, for whom only those with a high school education showed an inverse association between offspring education and depression symptoms. The findings underscore how offspring education is a potential resource for reducing disparities in health across families.